Match running performance is similar in lower and higher competitive standards of Spanish professional soccer accounting for effective playing time - Lago-Peñas, Carlos; García-Calvo, Tomás; López del Campo, Roberto; Resta, Ricardo; Ponce-Bordón, José Carlos (Biology of Sport, 2024)
This study aimed to compare match running performance of players in the top two competitive standards of Spanish professional soccer, accounting for effective playing time (the duration of play after subtracting the game interruptions). A total of 2,784 match observations from 44 teams competing in the Spanish First Division (LaLiga Santander) and the Second Division (LaLiga Smartbank) were undertaken during two consecutive seasons (from 2021/22 to 2022/23). Total distance (TD), medium-speed running (MSR, distance 14.1–21 km·h −1 ), high-speed running (HSR, > 21 km·h −1 ), very high-speed running (VHSR, 21.1–24 km·h −1 ) and sprinting speed running distance (Sprint, > 24 km· h −1 ) were analyzed using a computerized tracking system (TRACAB, Chyronhego, New York, NY). These physical performance variables were calculated for both total and effective playing time. The main results showed that the mean effective playing time was significantly higher in matches of the First Division than in the Second Division ( p < .01). In contrast to those observed when total playing time was considered, there were no significant differences ( p > .05) between both competitive standards on medium speed running (MSR), high speed running (HSR), very high-speed running (VHSR), and sprint distances when the effective playing time was considered. Such findings demonstrate that contrary to previous research match running performance of players was similar in lower and higher competitive standards. Thus, effective playing time should be taken into account when interpreting the match running performance of professional soccer players.